2011
DOI: 10.3991/ijac.v4i1.1519
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the Everyday Life into Engineering Education

Abstract: Abstract— To successfully design and engineer solutions for today’s and tomorrow’s rapidly changing and expanding global contexts, in which people are confronted with new opportunities and challenges each day, engineering programs should be training their students to become broad based professionals, who are aware of the actual needs, values and behaviors of the people that use their solutions in their everyday life, work or play. This article argues that in order to built such an awareness, engineering studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For example, educators need to adopt a different way of teaching by allowing engagement in project modules where students can become proactive problem solvers involving critical thinking. In addition, higher education institutions need to change their business models by supporting flexible learning, preparing students to meet real-world problems [82] and integrating them into the curriculum [83]- [84] 5 CONCLUSIONS This research's urgency is evident from the growing gap between students' expectations and what universities are able or willing to provide [85]. Therefore, the learning objectives of the project management course are focused on tools and techniques to master the life cycle and procedures of planning, initiation, evaluation and termination of the project, time-resource analysis, risks, changes and control mechanisms.…”
Section: Future Project Management Pedagogymentioning
confidence: 99%
“…For example, educators need to adopt a different way of teaching by allowing engagement in project modules where students can become proactive problem solvers involving critical thinking. In addition, higher education institutions need to change their business models by supporting flexible learning, preparing students to meet real-world problems [82] and integrating them into the curriculum [83]- [84] 5 CONCLUSIONS This research's urgency is evident from the growing gap between students' expectations and what universities are able or willing to provide [85]. Therefore, the learning objectives of the project management course are focused on tools and techniques to master the life cycle and procedures of planning, initiation, evaluation and termination of the project, time-resource analysis, risks, changes and control mechanisms.…”
Section: Future Project Management Pedagogymentioning
confidence: 99%
“…Early study [10] also showed most of students´ experienced better learning outcomes in terms of applying knowledge from one course to the others and seeing an entire picture of knowledge base. Others even more direct targeting the education programs directly toward profession job matching or job creating [7], or focusing on the real world integrating into the regular study curriculum [3]. Though some study [4] pointed out challengeable barriers, as poor communication, different priorities and lack of resources lack of a clear, convenient, coordinated system of contact in and across universities and potential industrial partners.…”
Section: Introductionmentioning
confidence: 99%
“…The future education curriculum is therefore not one of these, but combined all of four as a sustainable and complex whole. Other studies found the benefits of bring the real life experience into teaching [3], combining work and study [5], stating the need of various styles on lessons for learning outcomes [1] and practicing internal ship placement at the industries [2].…”
Section: Introductionmentioning
confidence: 99%